The Need for Sensory-Friendly “Zones”: Learning From Youth on the Autism Spectrum, Their Families, and Autistic Mentors Using a Participatory Approach - Clément, Marc-André; Lee, Keven; Park, Melissa; Sinn, Anabel; Miyake, Natalie (Frontiers in Psychology, 2022)
Hyperresponsive sensory processing has been linked to a diagnosis of autism spectrum disorder (ASD) before its inclusion as one of its core characteristics in the revised DSM-V. Yet, research focused on sensory processing and the participation of children and youth with ASD remains relatively scarce. Although the refinement of the International Classification of Functioning and Disability (ICF) relies on first-person accounts, longitudinal studies that foreground first-person autistic experiences of their own involvement in life situations are missing from this body of research. Objectives: In this sub-study, we drew from a longitudinal participatory research project consisting of two separately funded studies with children and youth with ASD and their families between 2014 and 2021. The participatory project used photovoice (PV) methods to identify the primary concerns related to socio-spatial exclusion (PV-1) and take action steps to redress them (PV-2). The objective of the sub-study was to understand what really mattered to children with autism, their parents, and autistic youth and adults to consider how their experiential knowledge could deepen our understanding of participation from their first-person perspectives. Materials and Methods: We used an overarching narrative phenomenological and aesthetic theoretical framework to focus data analysis on the bodily sensing experiences related to significant experiences or events, followed by an inductive thematic analysis of what mattered about those moments. Results: The topical areas of concern that emerged from analyses were: 1) the relationship between sensory experiences and mental health (motion madness); 2) the indivisibility or layering of sensory experiences (squishing & squeezing); 3) its impact when their ways to stay involved were categorically misunderstood (When you don’t respond in the correct way), and 4) how their care and consideration of others led to their innovative solutions for inclusion (I can’t be the only one). Listening to their bodily-sensing experiences in their own terms has implications for remapping the ICF and envisioning sensory curb-cuts to sustain participation from their first-person perspectives.